Pengembangan Perangkat Pembelajaran Fisika Berbasis Masalah untuk Meningkatkan Hasil Belajar dan Sikap Ilmiah Mahasiswa - I Wayan Gunada; Hairunnisyah Sahidu; Sutrio Sutrio (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
This study aims to develop problem-based learningÃÂ  device in terms ofÃÂ  validity and student responses. Learning device was developed coveringÃÂ  the syllabus, lesson plans, fundamental of physicsÃÂ  textbook, exsperiment in fundamental physics , worksheets, and learning outcome test. The expected benefits of this research is the problem-based learning tools that can be used as an alternative to the lecturer of the fundamental of physics learning in FKIPÃÂ  Mataram of University.This refers to the process of developing 4D models (define, design, develop, disseminate). The results validate the lecturer learning device consisting of a syllabus, lesson plans, fundamental of physicsÃÂ  textbook, experiment in fundamental physics , worksheets, and learning outcome test successivelyobtained scores of 2.65, 2.68, 3.30, 3.25, 2.285 and 3.14 are decent categorized. Student learning outcomes is seen from indicators of student achievement of cognitive learning and experiment processes valueÃÂ  row gets a percentage of 76.80%ÃÂ  and 78.50%, while the scientific attitudeÃÂ  students which amountedÃÂ  average value of 76.42 and scientific attitudeÃÂ  students can be interpreted good categorized. The positive student responses which amounted to 85.90%. From the validation results, student learning outcomes and student responses can be interpreted decentÃÂ  device.